RETRACTED: Pengaruh penerapan hypothetico-deductive reasoning dalam learning cycle terhadap keterampilan proses sains dan pemahaman konsep siswa - Yohn Ade Ardiyansyah; Paidi Paidi (Faculty of Mathematics and Natural Sciences, Universitas Negeri Yogyakarta, 2017)
RETRACTEDFollowing a rigorous and careful concerns and consideration in the review of the article published in Jurnal Inovasi Pendidikan IPA entitled “Pengaruh penerapan hypothetico-deductive reasoning dalam learning cycle terhadap keterampilan proses sains dan pemahaman konsep siswa” Vol 3, No 2, pp. 235-246, October 2017, DOI: http://dx.doi.org/10.21831/jipi.v3i2.9748This paper has been found to violate the principles of Jurnal Inovasi Pendidikan IPA Publication and has been retracted.The article has contained redundant material and throughout a careful examination, the editor has found that the paper has also been published in Jurnal Bioedukatika, Vol. 5, No. 1, pp. 29-38, 2017, DOI: http://dx.doi.org/10.26555/bioedukatika.v5i1.6027The document and its content have been removed from Jurnal Inovasi Pendidikan IPA, and reasonable effort should be made to remove all references to this article.